Dangerous and severe personality disorder : response and role of the psychiatric team - Bowers, Len, 1955- (Routledge, 2002)
This book provides details of the most effective ways of creating a positive context for working with personality disorder and contains a blueprint for training and organisational structures across the professional spectrum.